Vascular change in the placenta of diabetic mothers and hypertensive diabetic mothers - Rahman, MH; Sultana, SZ; Mannan, S; Sultana, S; Hossain, MA (Mymensingh Medical Journal, 2007)
Mymensingh Med J. 2006 Jul;15(2):176-9 The abstract of this article is available on the PubMed website